Delivery of magnetic resonance-guided single-fraction stereotactic lung radiotherapy - Finazzi, Tobias; van Sörnsen de Koste, John R.; Palacios, Miguel A.; Spoelstra, Femke O.B.; Slotman, Berend J.; Haasbeek, Cornelis J.A.; Senan, Suresh (Physics and imaging in radiation oncology, 2020)
•MR-guidance enables high precision single-fraction lung SABR delivery.•Breath-hold gating resulted in a mean tracked GTVt coverage of 99.6% during beam-on.•On-table plan adaptation improved PTV coverage, but had little impact on GTV doses.•Improved techniques are needed to allow for consistent MR-tracking of small tumors. Single-fraction stereotactic ablative radiotherapy (SABR) is an effective treatment for early-stage lung cancer, but concerns remain about the accurate delivery of SABR in a single session. We evaluated the delivery of single-fraction lung SABR using magnetic resonance (MR)-guidance. An MR-simulation was performed in 17 patients, seven of whom were found to be unsuitable, largely due to unreliable tracking of small tumors. Ten patients underwent single-fraction SABR to 34 Gy on a 0.35 T MR-linac system, with online plan adaptation. Gated breath-hold SABR was delivered using a planning target volume (PTV) margin of 5 mm, and a 3 mm gating window. Continuous MR-tracking of the gross tumor volume (GTVt) was performed in sagittal plane, with visual patient feedback provided using an in-room monitor. The real-time MR images were analyzed to determine precision and efficiency of gated delivery. All but one patient completed treatment in a single session. The median total in-room procedure was 120 min, with a median SABR delivery session of 39 min. Review of 7.4 h of cine-MR imaging revealed a mean GTVt coverage by the PTV during beam-on of 99.6%. Breath-hold patterns were variable, resulting in a mean duty cycle efficiency of 51%, but GTVt coverage was not influenced due to real-time MR-guidance. On-table adaptation improved PTV coverage, but had limited impact on GTV doses. Single-fraction gated SABR of lung tumors can be performed with high precision using MR-guidance. However, improvements are needed to ensure MR-tracking of small tumors, and to reduce treatment times.